Importance of Total Coupon in Utility Maximization: A Sensitivity Analysis - Devajit Mohajan; Haradhan Kumar Mohajan (Law and Economy, 2022)
This study takes an attempt to discuss utility maximization policies. The property of a commodity that enables it to satisfy human wants is called utility. The sensitivity analysis is included in the operation to show optimal policy of an organization. This study deals with four commodities and two constraints, such as budget constraint, and coupon constraint. The economic predictions of future production are necessary for the sustainable production. In the study Lagrange multipliers technique is applied to operate 6×6 bordered Hessian and 6×10 Jacobian appropriately. The sensitivity analysis between commodity and total budget are discussed with detail mathematical analysis.